Inhibitory Effect of r-Hirudin Variant III on Streptozotocin-Induced Diabetic Cataracts in Rats - Xiaojian Gong; Qiuyan Zhang; Shuhua Tan (The Scientific World Journal)
The in vivo inhibitory effect of r-hirudin variant III (rHV3) on streptozotocin (STZ)-induced diabetic cataracts in rats was investigated. SD-rats were firstly made diabetic by a single intraperitoneal injection of 2% (W/V) STZ (65 mg/kg). Two weeks later, cataract formation was examined by slit lamp microscope, and the cataracted animals were randomly grouped. The animals in the treated groups received rHV3 drops administration to the eyes with various doses. After 4 weeks treatment, the animals were sacrificed to evaluate the biochemical changes of aldose reductase (AR), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and malondialdehyde (MDA) levels in the eye lens. Meanwhile, the cataract progression was monitored by slit lamp microscope. As a result, rHV3 drops treatment significantly increased the activities of SOD and GSH-Px in the lens in a dose-dependent manner, whereas AR activity and MDA level in the lens were dramatically decreased. Also, the morphological observation further confirmed the inhibition of the development of STZ-induced diabetic cataracts by the rHV3 drops treatment. Thus, our data suggest that rHV3 drops are pharmacologically effective for the protection against STZ-induced diabetic cataracts in rats.